(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2023)
The pandemic years have witnessed extensive experimentation in the field of live performance, which has seen the emergence of new artistic forms by exploiting the potential, but also the limitations, of digital platforms. This essay aims to outline the nature of Online Unidentified Theatrical Objects (OTONI) as a distinctive reality, analyzing them through the concept of mediatization. The mediatization of OTONI involves both their dramma-turgical and performative forms, being characterized by a new kind of empathetic pact with the spectator, by their deterritorialized and ephemeral now everywhere nature, and by the assimilation of digital logics and languages in both formal structuring and dramaturgy.